Noninvasive monitoring of intracranial pressure after cardiac surgery: case report (Research, Society and Development, 2022)
Background: Heart valves are important structures that play an essential role in directing blood flow; changes in the functioning of these structures may require cardiac surgery with cardiopulmonary bypass. The behavior of intracranial pressure (ICP) in patients undergoing this type of surgery is unknown. Objective: aim of this study was to report alterations in the waveform morphology of ICP in a patient submitted to cardiac surgery with cardiopulmonary bypass.  Case Description: This report provides data on ICP waveform morphology (P1 and P2 peaks) monitored before, immediately after, and on the 5th day after cardiac surgery. In the preoperative evaluation, the morphology of the patient's ICP waveforms was slightly altered, possibly due to the underlying cardiovascular disease. In the second measurement of the ICP waveforms, performed after surgery, the wave morphology of the ICP was normal. On the 5th PO day, after the patient presented clinical signs of neurological complications, the third ICP measurement was performed, which showed that the morphology of the ICP wave was altered.Conclusions: The use of non-invasive monitoring of ICP is of great importance in patients undergoing cardiac surgery, with the aim of diagnosing, preventing and/or enabling rapid treatment in cases where there is an evolution of more severe neurological complications that may lead to death.